Restoring hope : conversations on the future of Black America - West, Cornel; Sealey, Kelvin Shawn; Obsidian Society (Boston, Mass. : Beacon Press, 1997)
Perhaps the most prominent public intellectual of our time, Cornel West asks nine of America's most influential artists, scholars, and public figures about the sources of hope among African Americans today: "How can we be realistic about what this nation is about and still sustain hope, acknowledging that we're up against so much?"
Foreword / Henry Louis Gates, Jr. -- Preface / Cornel West -- Introduction / Kelvin Shawn Sealey -- Harry Belafonte -- Bill Bradley -- Charlayne Hunter-Gault -- The Reverend Dr. James A. Forbes, Jr., and the Reverend Dr. James M. Washington -- Wynton Marsalis -- Patricia Williams -- Haki Madhubuti -- Maya Angelou -- "Catch the Fire" / Sonia Sanchez -- The Obsidian Society.
"A project of the Obsidian Society."
Keywords: African Americans -- Social conditions; African Americans -- Conduct of life; African Americans -- Interviews; Celebrities -- United States -- Interviews; United States -- Social conditions -- 1945-